Training in elite young athletes (the Training of Young Athletes (TOYA) Study): injuries, flexibility and isometric strength - Maffulli, N.; King, J. B.; Helms, P. (British Journal of Sports Medicine, 1994)
Using a mixed longitudinal design, the incidence of injuries, and the development of flexibility and isometric strength of the upper and lower limbs were studied for 2 years in 453 elite young athletes (aged between 9 and 18 years) practising football, gymnastics, swimming or tennis. The children suffered from a low incidence of injuries. Strength and flexibility did not exert a significant role in determining injuries. The rate of injury was not significantly different between the 2 years of the study. Young swimmers showed a greater generalized flexibility. Girls were more flexible than boys between the ages of 13 to 16 years. Athletic children are able to exert greater isometric strength than normal schoolchildren. Boys diverged from the normal population at 14 years, while athletic girls were stronger at all ages. Girls were stronger than boys up to age 12, who were still increasing their muscle strength at 19 years. The average maximal isometric strength exerted in both upper and lower limbs in the four sports was not significantly different. Male gymnasts over 11 years old were significantly stronger than all other athletes.